Ontela PicDeck (B) : customer segmentation, targeting, and positioning - Sawhney, Mohanbir S. (SAGE knowledge. Cases., 2016)
Ontela, a technology start-up company, has introduced an innovative service called PicDeck that improves the mobile imaging experience for wireless subscribers. Ontela sells PicDeck to wireless carriers, who in turn private-label the service to their subscribers. Ontela must decide which customer segments it should target for the service and how to create a positioning strategy and a marketing communication plan to promote it. This case outlines the factors which will influence Ontela's strategy.